Aplikasi E Commerce Spare Parts Mesin Diesel Berbasis Website Pada Toko Lancar Diesel - Matthew Rene,; Ery Dewayanti, (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
In today's digital era, the use of technology in business operations is very important to increase efficiency and market reach. Toko Lancar Diesel, which sells diesel engine spare parts, has not yet switched to digitalization, which has resulted in a lack of efficiency in managing its business. To overcome this, a website-based sales information system is needed that can increase the efficiency and effectiveness of store operations. This research designs a website-based sales application using Html, CSS, PHP and MySQL database, which will help manage stock, transactions and financial reports in real-time. The use of the Scrum methodology in developing this website ensures that the process runs more structured and will be using scrum as methodology. This website consists of one main part: a public website that facilitates online sales of spare parts.